Sinus lift associated with leucocyte‐platelet‐rich fibrin (second generation) for bone gain: a systematic review - Otero, Ada Isis Pelaez (2022)
The purpose of this systematic review was to analyze sinus lifting procedures and to compare the efficiency of this treatment associated with the second generation of platelet‐rich fibrin related to its effects on bone gain and to clarify the regenerative efficacy in sinus lift procedure, whether alone or as a coadjutant to other bone graft materials. The PICOT question was, “In clinical studies with patients needing a maxillary sinus lift (P), does the use of PRF either alone (I) or in conjunction with other biomaterials (C) improve the clinical outcome associated with bone gain and density (O), with at least three months of follow‐up (T)?” An electronic search was conducted in the MEDLINE (PubMed), Science Direct, and Scopus databases through a search strategy. A total of 443 articles were obtained from the electronic database search. Sixteen articles met all criteria and were included in this review. Within the limitation of this study and interpreting the results carefully, it was suggested that a higher risk for implant failure after a sinus elevation might be seen in patients with residual bone ≤4 mm, and PRF application was effective, suggesting reducing the time needed for new bone formation.